Analisis Pemanfaatan Bonggol Jagung Menjadi Bioetanol untuk Energi Alternatif - Sandoris, Satria; Gusnita, Novi (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2025)
Corn production produces waste in the form of corn cobs that have not been optimally utilized, even though they contain complex carbohydrates that can be converted into Bioethanol. The problem faced is the cessation of the use of agricultural waste as an alternative energy source, especially in the context of direct conversion into electrical energy. This study aims to analyze the potential for converting corn cob waste into Bioethanol and then calculate the potential electrical energy that can be generated from a mixture of Bioethanol and gasoline (E0, E10, E15, E20) through simulation using Aspen Plus V10 software. The results show that from 825 kg of corn cob waste per ton of plant, 58.5684 L/hour of Bioethanol can be produced, with the highest electrical energy potential of 542.42 kWh in the E20 mixture. Utilization of corn cob waste as Bioethanol offers an environmentally friendly and sustainable renewable energy solution.Keywords – Bioethanol, Corn Humps, Energy, Fermentation.